Thematic Tafsir Approach to the Six Principles of Qaulan in Addressing Digital Hate Speech - Abdullah Hasan; Ainur Rhain (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The phenomenon of the proliferation of hate speech on social media constitutes an important background for this study. The low level of digital communication ethics, accompanied by the high intensity of hate speech in cyberspace, has encouraged the author to examine this phenomenon through a Qur’anic perspective. Ideally, communication between individuals and groups should reflect the values of respect, gentleness, and truth as taught in the Qur’an through the concepts of qaulan kariman, qaulan layyinan, qaulan ma‘rufan, and others. This article employs a conceptual thematic exegesis approach to analyse verses that prohibit hate speech and a Systematic Literature Review (SLR) by examining literature from 2015–2024 within the framework of thematic-conceptual interpretation. The main findings indicate that the Qur’an not only condemns hate speech, but also offers practical guidance on ethical communication in society, including in the digital era. Therefore, the implementation of Qur’anic values serves as a moral and social solution in fostering a healthy, peaceful, and civilised space of interaction amidst the advancement of information technology.